N-Terminal Acetylation Stabilizes SIGMA FACTOR BINDING PROTEIN1 Involved in Salicylic Acid-Primed Cell Death. Issue 1 (5th March 2020) - Li, Zihao; Dogra, Vivek; Lee, Keun Pyo; Li, Rongxia; Li, Mingyue; Li, Mengping; Kim, Chanhong
Abstract : N-terminal acetylation regulates SIB1 protein stability to ensure its function in salicylic acid-primed cell death. Abstract: N-terminal (Nt) acetylation (NTA) is an ample and irreversible cotranslational protein modification catalyzed by ribosome-associated Nt-acetyltransferases. NTA on specific proteins can act as a degradation signal (called an Ac/N-degron) for proteolysis in yeast and mammals. However, in plants, the biological relevance of NTA remains largely unexplored. In this study, we reveal that Arabidopsis ( Arabidopsis thaliana ) SIGMA FACTOR-BINDING PROTEIN1 (SIB1), a transcription coregulator and a positive regulator of salicylic acid-primed cell death, undergoes an absolute NTA on the initiator Met; Nt-acetyltransferase B (NatB) partly contributes to this modification. While NTA results in destabilization of certain target proteins, our genetic and biochemical analyses revealed that plant NatB-involved NTA instead renders SIB1 more stable. Given that the ubiquitin/proteasome system stimulates SIB1 degradation, it seems that the NTA-conferred stability ensures the timely expression of SIB1-dependent genes, mostly related to immune responses. Taking our findings together, here we report a noncanonical NTA-driven protein stabilization in land plants.